Assistance of Cadres in the Delivery Planning and Complication Prevention Program in Bandar Lor Village, Working Area of Sukorame Public Health Center - Titisari, Ira; Yanuarini, Triatmi Andri (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
Pregnant women will face both minor and severe emergencies at every birth. The low access to quality maternal and newborn health service is one of the factors that greatly influence the occurrence of maternal and infant mortality, therefore it is not sufficient to only support good programs but also requires the care of the surrounding community. The service method was carried out by providing booklets, lectures, giving questions and answers, also pretest and posttest. This activity was carried out at the Bandar Lor village hall with a total of 25 respondents. The result of the pretest showed that 48Percent of cadres had a good level of knowledge, 44Percent were insufficient category and 8Percent were in the poor category. After the lecture was carried out, there were 84Percent in good knowledge, 12Percent were insufficient category and 4Percent were in the poor category. Based on these results, this community service, there was a change in knowledge of cadres before and after community service was held